Alterations in gene transcription patterns associated with the Development of isometamidium resistance in Trypanosoma congolense - Konde, V.; Majiwa, Phelix A.O. (European Union, 2000)
In order to search for T. congolense genes whose transcription status may be influenced by response to isometamidium chloride, we applied the Representational Difference Analysis (RDA) (Lisitsyn et al., 1993; Hubank & Schatz, 1994) to the comparative analysis of cDNA synthesised from two isogenic trypanosome clones, the isometamidium chloride sensitive T. congolense ILI 180 (Nantulya et al., 1984) and its resistant derivative, IL3343 (Peregrine et al., 1997). Three major categories of genes were found: (i) those transcribed only in the trypanosome clone sensitive to isometamidium chloride, (ii) those transcribed more abundantly in only one of the two isogenic trypanosome clones, and (iii) those that are transcribed at approximately the same level, but which detect highly polymorphic loci in the isogenic trypanosome clones.